Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM 4(2) August 2022 publishs 3 papers related to Covid-19 and 2 papers related soil mechanics for infrastructures. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the fourth volume second issue.